2021
DOI: 10.3390/foods10020373
|View full text |Cite
|
Sign up to set email alerts
|

Preharvest Application of Chitosan Improves the Postharvest Life of ‘Garmrok’ Kiwifruit through the Modulation of Genes Related to Ethylene Biosynthesis, Cell Wall Modification and Lignin Metabolism

Abstract: The influence of the preharvest application of chitosan on physicochemical properties and changes in gene expression of ‘Garmrok’ kiwifruit during postharvest cold storage (0 °C; RH 90–95%; 90 days) was investigated. Preharvest treatment of chitosan increased the fruit weight but had no significant effect on fruit size. The chitosan treatment suppressed the ethylene production and respiration rate of kiwifruit during the cold storage. The reduction of ethylene production of chitosan-treated kiwifruit was accom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…The inhibition of respiration rate coupled with reduced metabolic activity reduces the synthesis and utilization of metabolites, thereby delaying the degradation of starch to sugars ( Kumarihami et al., 2022 ). Similar results were found in kiwifruit ( Kumarihami et al., 2021 ). Our study showed that chitosan coating could alleviate chilling injury by enhancing AMY and BMY activities and accelerating starch degradation in melon during the later stages of cold storage.…”
Section: Discussionsupporting
confidence: 88%
“…The inhibition of respiration rate coupled with reduced metabolic activity reduces the synthesis and utilization of metabolites, thereby delaying the degradation of starch to sugars ( Kumarihami et al., 2022 ). Similar results were found in kiwifruit ( Kumarihami et al., 2021 ). Our study showed that chitosan coating could alleviate chilling injury by enhancing AMY and BMY activities and accelerating starch degradation in melon during the later stages of cold storage.…”
Section: Discussionsupporting
confidence: 88%
“…Such an effect of high CO 2 and low O 2 concentrations on decreasing the ethylene production during storage has been reported in Pyrus communis [ 72 ]. It has been recently reported that chitosan treatment suppressed ethylene production during the cold storage of kiwifruits, and the reduction of ethylene was accompanied with the suppressed expression of ethylene biosynthesis genes [ 73 ]. Similarly, chitosan treatment suppressed the expression of FaACS and FaACO genes that were involved in ethylene biosynthesis, which reduced the softness, increased the shelf life and positively influenced the retention of various quality attributes of strawberries [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, lower TSS with preharvest applications of chitosan was reported in tomato by Migliori et al. (2017) and in kiwifruit by Kumarihami et al. (2021) .…”
Section: Resultsmentioning
confidence: 97%